COUNTERMAJORITARIAN INSTITUTIONS IN THE RUSSIAN CONSTITUTION OF 1993 AS AN INSTRUMENT ENSURING CONSTITUTIONAL AND POLITICAL STABILITY - S. Shakhray; S. Popova (BRICS Law Journal, 2018)
The article enriches the discussion on the legal reasons and conditions fostering the viability of democratic constitutions by analyzing the rich experience of the Russian Constitution of 1993. Particular attention is paid to the concept of countermajoritarian institutions. The authors elaborate the idea that countermajoritarian institutions can play an important role in ensuring the viability (put in other terms, the proper balance between stability, adaptability, and dynamic development) of modern democratic constitutions as well as political regimes.The article presents evidence-based data showing that the President and the Constitutional Court of the Russian Federation systematically acted as countermajoritarian institutions at the initial stage of the implementation of the “blueprint for the future” set down in the 1993 Russian Constitution. As a result of the activities of these institutions, strong legal frameworks were created that are necessary for the establishment of anew constitutional system of the Russian state and law.Today, the Russian Constitution of 1993 is one of the longest lasting democratic constitutions in the world (the average “life expectancy” of democratic constitutions adopted over the past 250 years is about seventeen years). The study of the countermajoritarian provisions in the 1993 Russian Constitution is of both theoretical and practical importance. In particular, the results of the study can be useful in creating efficient legal instruments for the maintenance of political stability and social development management both within sovereign states and within interstate communities.